Explosion Box: A Learning Media of Ecosystem Components for Elementary School Student - Nasriya, Tsalats Zaidatul; Wuryandani, Wuri; Mulyono, Mulyono (FKIP Universitas Lampung, 2021)
Abstract: Explosion Box as Learning Media of Ecosystem Components for Elementary School Student. Objective: This research aims to describe the development of explosion box as learning media to deal with bored student in science learning to use textbooks. Method: Development of learning media in this study is implementing the Borg & Gall. Field test were conducted on 5th grade elementary school students in Blitar, Indonesia. Finding: The results showed that the Explosion Box as learning media was valid category with a material expert validation: 93.3%; design expert validation: 90%; expert validation: 90%. Results of trials: small group is 95.4% and large group is 94.4%. Data pre-test and post-test results: before using product is 70.3 and after using product is 85.9. Conclusion: Expert validation and student response questionnaires revealed that Explosion Box as learning media was very interesting and useful so that students do not get bored in the learning process. Keywords: Explosion Box, elementary school student, learning media. DOI: http://dx.doi.org/10.23960/jpp.v11.i2.202115